2019
DOI: 10.15405/epsbs.2019.04.02.73
|View full text |Cite
|
Sign up to set email alerts
|

Examining The Link Between Resilience, Burnout And Stress

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This finding supported by the theory that many factors potentially cause preservice teachers to experience academic burnout [14,26]. This finding is supported by several studies, which showed that different factors could affect university students experiencing burnout [38,129,130].…”
Section: Discussionsupporting
confidence: 78%
“…This finding supported by the theory that many factors potentially cause preservice teachers to experience academic burnout [14,26]. This finding is supported by several studies, which showed that different factors could affect university students experiencing burnout [38,129,130].…”
Section: Discussionsupporting
confidence: 78%
“…Resilience, defined at the end of the 20th century [30,31], can be considered a strategy put in place to cope with stressful situations [24,[32][33][34]. It is the ability to be able to adapt to adverse situations [15,[35][36][37]. Aspects such as people's positive emotions (happiness, optimism, self-esteem, and assertiveness that the individual possesses) will be fundamental in the face of these problematic situations [38,39].…”
Section: Resiliencementioning
confidence: 99%